VARIATION OF THE MEDIAN NERVE COURSE AND ITS CLINICAL IMPORTANCE - Haviarova, Zora; El Falougy, Hisham; Killingerova, Anna; Matejcik, Viktor (Biomedical papers, 2009)
Aims and methods: In our work we present and describe the variation of the course of the median nerve found in both upper limbs of one of the cadavers in our Institute of Anatomy (Medical Faculty, Comenius University, Bratislava, Slovakia) during the students dissection of the peripheral nerves and vessels. Results and conclusion: This non-standard course of the median nerve was compared with a standard course described in the anatomical literature and atlases, and confronted with the variations of the median nerve found and its course described in the available literature. We also provide some clinical implications of such peripheral nerve variability because understanding such anomalies is important in the diagnosis of unexplained clinical signs and symptoms as well as during nerve blocks and certain surgical procedures around the neck and proximal arm.
Keywords: Variation/Course/Median Nerve/Formation